Sialic acid-based probiotic intervention in lactating mothers improves the neonatal gut microbiota and immune responses by regulating sialylated milk oligosaccharide synthesis via the gut–breast axis - Yushuang Wang; Binqi Rui; Xiaolei Ze; Yujia Liu; Da Yu; Yinhui Liu; Zhi Li; Yu Xi; Xixi Ning; Zengjie Lei; Jieli Yuan; Liang Li; et al. (Gut Microbes, 2024)
ABSTRACTHuman milk oligosaccharides (HMOs) are vital milk carbohydrates that help promote the microbiota-dependent growth and immunity of infants. Sialic acid (SA) is a crucial component of sialylated milk oligosaccharides (S-MOs); however, the effects of SA supplementation in lactating mothers on S-MO biosynthesis and their breastfed infants are unknown. Probiotic intervention during pregnancy or lactation demonstrates promise for modulating the milk glycobiome. Here, we evaluated whether SA and a probiotic (Pro) mixture could increase S-MO synthesis in lactating mothers and promote the microbiota development of their breastfed neonates. The results showed that SA+Pro intervention modulated the gut microbiota and 6’-SL contents in milk of maternal rats more than the SA intervention, which promoted Lactobacillus reuteri colonization in neonates and immune development. Deficient 6’-SL in the maternal rat milk of St6gal1 knockouts (St6gal1−/−) disturbed intestinal microbial structures in their offspring, thereby impeding immune tolerance development. SA+Pro intervention in lactating St6gal1± rats compromised the allergic responses of neonates by promoting 6′-SL synthesis and the neonatal gut microbiota. Our findings from human mammary epithelial cells (MCF-10A) indicated that the GPR41-PI3K-Akt-PPAR pathway helped regulate 6′-SL synthesis in mammary glands after SA+Pro intervention through the gut – breast axis. We further validated our findings using a human-cohort study, confirming that providing SA+Pro to lactating Chinese mothers increased S-MO contents in their breast milk and promoted gut Bifidobacterium spp. and Lactobacillus spp. colonization in infants, which may help enhance immune responses. Collectively, our findings may help alter the routine supplementation practices of lactating mothers to modulate milk HMOs and promote the development of early-life gut microbiota and immunity.